Soil health implications of some d-block metals in selected agricultural soils in Southeast Nigeria - Ofem, Kokei Ikpi; Kefas, Patrick Katan; Abam, Prince Okori; Ediene, Victoria Francis; John, Kingsley; Pawlett, Mark (Springer, 2023)
Soil fertility, soil health and environmental management through the estimation of background concentration of potentially toxic elements is required for environmental safety. This study aims at investigating the concentration, fertility and potential health risks of some d-block metals (Ti, V, Fe, Mn, and Mo) in some agricultural soils, and establishes the relationship between the metals and some soil properties. Eight elevation ranges resulted from the digital elevation models of the study area; two in Ishibori (NG1, NG2), three each in Agoi-Ibami (CG1, CG2, CG3) and Mfamosing (SG1, SG2 and SG3). One soil profile pit was sunk along each of the elevations. Thirty-five composite soil samples were collected at 0–30, 30–60, 60–90, 90–120, 120–150, 150–180 and 180–200 cm depending on soil depth. Only the profile means of Mn (660.82 ± 612.89 mg/kg) and Mo (2.61 ± 0.73 mg/kg) exceeded permissible concentrations and would pose threats to the environment. Also, the concentrations of the d-block metals exceeded permissible values in Ishibori making them prone to toxicity. The metals were irregularly distributed with depth; however, Mn and Fe were concentrated in the subsurface soils. Clay and sand contents correlated positively and negatively, respectively with all the d-block metals at p < 0.05. The linear model was more efficient in estimating V and Mo via soil properties with adjusted R2 of 33 – 67% for the metals. In conclusion, agricultural activities and geology may influence the accumulation of d-block metals, hence the call for environmental monitoring to curtail metals’ assimilation by crops.
Keywords: Agricultural Geography; Soil Chemistry; Soil and Water Protection; Soil Microbiology; Soil Physics; Soil Science